THE INFLUENCE OF STORE IMAGE, STORE ATMOSPHERE AND SOCIAL MEDIA MARKETING ON PURCHASE DECISIONS AT SMARTPHONE RETAIL STORES IN PEKANBARU - Tiufany, Britney; Lina, Lina (International Journal of Application on Economics and Business, 2024)
This research aims to determine the influence of store image, store atmosphere, and social media marketing on purchasing decisions at one of the smartphone retails stores in Pekanbaru. The research method is using quantitative approach by distributing questionnaires through offline and online to customers who had made purchases at the store during the period from July - September 2023. The sampling method used a non-probability sampling technique where not all populations have an equal chance with purposive sampling method, which involves the selection of samples based on specific considerations, in a total of 185 respondents. The data analysis technique utilized the Structural Equation Modeling (SEM) model with the Smart PLS 3.0 application. The results of this study indicate a positive and significant influence of store image, store atmosphere, and social media marketing on purchasing decisions at the smartphone retail store. This research provides insights for the store owner to strengthen the store's image, improve the store atmosphere, and effectively utilize social media to positively influence purchasing decisions. The practical implications of this research can assist the retail store in enhancing marketing strategies and store management to increase attractiveness and purchasing decisions.